The influence of Organizational Culture and Teamwork on Employee Engagement: Role of Achievement Motivation as a Mediation - Novendi Simbolon; Mafizatun Nurhayati (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This study aims to determine the influence of organizational culture, teamwork on employee engagement mediated by achievement motivation. The method used in this study is quantitative research. The population in this study is halo BCA employees who work for more than a year total 292 employees. The sampling technique using accidental sampling (convenience sampling) with the slovin formula was obtained by 168 respondents. Data analysis using SEM PLS (Partial Least Square) analysis technique. The results showed that organizational culture variables, achievement motivation had a positive and significant effect on employee engagement. Teamwork does not have a positive effect on employee engagement, and teamwork through mediation of achievement motivation has a positive and significant effect on employees, as well as mediated by achievement motivation, organizational culture and teamwork can strengthen the influence on employee engagement at halo BCA BSD. Keywords: Organizational Culture, Teamwork, Achievement Motivation, Employee Engagement